THE RELATIONSHIP BETWEEN HUSBAND'S KNOWLEDGE AND SUPPORT WITH PREGNANT WOMEN'S ANTENATAL CARE (ANC) VISIT COMPLIANCE IN THE PARIAMAN COMMUNITY HEALTH CENTER WORK AREA - MAIFITA, YESI; ZAYANI, NOFRI; ZANAH, MIFTAKHUL (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2025)
Pregnancy for a woman is the most difficult phase in her life, especially for primiparous mothers. Routine pregnancy check-ups can prevent high-risk pregnancies such as preeclampsia and even maternal and fetal death. Husband's knowledge and support are supporting factors that can motivate pregnant women's compliance in undergoing pregnancy check-ups. This study aims to determine the relationship between husband's knowledge and support with compliance in conducting antenatal care (ANC) visits in pregnant women in the Pariaman Health Center Work Area. This type of research is quantitative with a cross-sectional study approach. The study was conducted on July 26-August 26, 2024. The population in this study were husbands of pregnant women who underwent ANC examinations at the Pariaman Health Center. The research sample was determined as many as 42 husbands of pregnant women by random sampling. Statistical tests using Chi Square at the α level = 5%. The results of the study showed that more than half of the respondents, namely 26 people (61.9%) had good knowledge, and supported their wives to have ANC examinations, namely 22 people (52.4%), and as many as 27 people (64.3%) were compliant in making Antenatal Care (ANC) visits. The results of the Chi square test on the knowledge aspect showed a p-value = 0.01 <α = 0.05, while on the support aspect the p-value was obtained = 0.03 <α = 0.05. In conclusion, there is a relationship between husband's knowledge and support with compliance with Antenatal Care visits in the Pariaman Health Center Work Area. Suggestions, further researchers from the health sector can provide counseling activities to husbands of pregnant women regarding the importance of conducting examinations during pregnancy in order to maintain the health and safety of the mother and fetus